Prunus persica. Peach and nectarine - Pérez-Clemente, Rosa M.; Ríos, Gabino; Badenes, María L.; Canas, Luis A. (CABI (Centre for Agricultural Bioscience International), 2021)
This chapter discusses the botany and history, breeding and genetics, molecular genetics, gene cloning, functional genomics, fruit characteristics, micropropagation, micrografting, somatic cell genetics, genetic manipulation, genetic transformation and cryopreservation of peach and nectarine.